Pencegahan Cyberbullying di Era Digitalisasi di Sekolah SMPN 2 Kemlagi Kabupaten Mojokerto - Eny Nuraeni; Hasyim Muarifin; Nasikhatus Syairiyah; Muhammad Nurul Afani; Alwi Shihab Amirrulloh Kartono Putra; Oktaberto Dwi Christianto; Muslim Tri Efendi; Miftakhul Mufidah; Lutvia Tri Waluyo; Aprilliyani Khayrunnisa; Rr Icha Hizkia Dewardhani; Dinda Tri Mulyani Lestari; Ferdian Martino Rizky Pradana; Riza Dwi Ervina; Yunia Eka Purwanti; Wiwin Novi Anjani; Marsadila Elok Nur Latifa; Chynta Deyna Zein; Devi Damayanti; Rossalia Nadia Sari; Miftakhul Jannah; Arif Wibowo Wonomiharojo; Sultan Muhammad Raihan (Jurnal Nusantara Berbakti, 2025)
This community service program aims to prevent cyberbullying in Mojorejo Kemlagi Village and provide students with an understanding of the dangers posed by cyberbullying. The steps to prevent cyberbullying are not sharing posts too often, reducing irrelevant comments, limiting the use of social media, and not being easily provoked. The result of this community service is an effort to prevent cyberbullying in the modern era with the understanding of SMP Negeri 2 Kemlagi students.